Testing spore amyloidity in Agaricales under light microscope: the case study of Tricholoma - Alfredo Vizzini; Giovanni Consiglio; Ledo Setti (IMA Fungus)
Abstract Although species of the genus Tricholoma are currently considered to produce inamyloid spores, a novel standardized method to test sporal amyloidity (which involves heating the sample in Melzer’s reagent) showed evidence that in the tested species of this genus, which belong in all 10 sections currently recognized from Europe, the spores are amyloid. In two species, T. josserandii and T. terreum, the spores are also partly dextrinoid. This result provides strong indication that a positive reaction of the spores in Melzer’s reagent could be a character shared by all genera in Tricholomataceae s. str.